Analiz dejstvij L. Messi s mjacom v igrach Kubkov Mira FIFA 2014 i 2018 gg. - Chirva, B. G.; Kozlov, V. S.; Zmievskaya, E. S. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article is devoted to the analysis of the materials about the game of L. Messi - one of the best football players in the world - in games of World Cup 2014 and 2018 years. The main purpose of this research is collecting statistical data about analysis of the game by L. Messi with the ball. Specifically, the amount and ratio of the episodes of games, in which he controls the ball by touching it one, two or three and more touches. And amount and ratio of game episodes, when he controls the ball by different foots. Based on this data it is possible to characterize the individual style of playing the game by this football player and evaluate the validity of the assumptions about ball controlling tendencies in football evolution to make adjustments in training of the youth football players and game of professional teams.